2004
DOI: 10.1529/biophysj.104.048868
|View full text |Cite
|
Sign up to set email alerts
|

LexA-DNA Bond Strength by Single Molecule Force Spectroscopy

Abstract: The SOS system of Escherichia coli is coordinated by two proteins: LexA, a repressor protein of several unlinked genes, and the coprotease RecA. As known to date LexA controls 31 genes with slightly different DNA binding motifs allowing for a variable degree of repression from one gene to the other. Besides the SOS system LexA plays an important role in the regulation of transcription. The protein regulates transcription by using particular motifs to bind DNA, the helix-turn-helix motif. Here, we employed AFM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 51 publications
(69 reference statements)
6
72
0
1
Order By: Relevance
“…This suggests that for physical reaction-radii of one nanometer or less the reaction-diffusion master equation may be a good approximation to a diffusion limited reaction. While physical reaction-radii have not been experientially determined for most biological reactions, it has been found experimentally that the LexA DNA binding protein has a physical binding potential of width ∼ 5Å [30]. We caution, however, that these results are only valid for the truncated perturbation expansions, and do not necessarily hold for the error between the exact solutions p h (x, t) and p(x, t).…”
Section: Error Between Asymptotic Expansions Of the Scdlr Modelmentioning
confidence: 88%
“…This suggests that for physical reaction-radii of one nanometer or less the reaction-diffusion master equation may be a good approximation to a diffusion limited reaction. While physical reaction-radii have not been experientially determined for most biological reactions, it has been found experimentally that the LexA DNA binding protein has a physical binding potential of width ∼ 5Å [30]. We caution, however, that these results are only valid for the truncated perturbation expansions, and do not necessarily hold for the error between the exact solutions p h (x, t) and p(x, t).…”
Section: Error Between Asymptotic Expansions Of the Scdlr Modelmentioning
confidence: 88%
“…Several experiments also have been performed with DNA strands [1078,[1143][1144][1145][1146], DNA-ligands [1147][1148][1149][1150], RNA [1151], RNA-ligands [1152], peptides [1153], and other complementary molecules [389,1154,1155]. In particular, Schumakovitch et al [1156] have studied the temperature dependence of unbinding forces between complementary DNA strands.…”
Section: Rupture Force Of Specific Interactionsmentioning
confidence: 99%
“…[15] The direct investigation of specific, native protein-DNA interactions has been reported recently. [23][24][25] In our studies reported herein, we applied AFM singlemolecule force spectroscopy to study the specific binding between the peptides listed in Table 1 and the DNA target sequence. Each peptide was covalently immobilized to an amino-functionalized mica surface in a directed manner with the short C-terminal linker 1,8-diamino-3,6-dioxaoctane and the cross-linker BS 3 (bis(sulfosuccinimidyl)suberate; Figure 1 b).…”
mentioning
confidence: 99%